Blue Tourism and Community Welfare in Coastal Indonesia: Evidence from Bone Regency - Hamzah, Firman; Hasnawati, Hasnawati; Irmawati, Irmawati; Ismail, Ismail; Marhati, Marhati (Universitas Medan Area, 2025)
This study investigates how blue tourism contributes to community welfare in Bone Regency, South Sulawesi, Indonesia. Despite the region’s rich marine and cultural resources, such potential has not optimally utilized to support sustainable development. Using a qualitative case study design, data were collected through in-depth interviews, field observations, and document analysis involving 15 local stakeholders, including tourism actors, village officials, community leaders, and micro- entrepreneurs. The findings highlight that local communities play a central role in developing blue tourism by mobilizing natural and cultural assets such as beaches, sunset spots, seafood cuisine, and homestays. Youth and women emerge as the main drivers of promotion and small-scale businesses, while village governments act as facilitators despite budget constraints. Key challenges include limited infrastructure, poor accessibility, and weak promotion, which restrict the sector’s growth. Nevertheless, blue tourism has created new livelihood opportunities, diversified household incomes, and strengthened social cohesion in coastal communities. This study concludes that community-based blue tourism has significant potential to improve economic and social welfare, but requires stronger institutional support, infrastructure investment, and inclusive governance. The findings contribute to the literature on the blue economy and sustainable tourism by emphasizing the integration of local participation, cultural values, and multi-stakeholder collaboration in coastal development.